Human and mouse specific T-cell helper factors assayed in vivo and in vitro: implications for human Ir genes. - Woody, J; Zvaifler, N; Reese, A; Ahmed, A; Hartzman, R; Strong, M; Howie, S; Kantor, F; Feldmann, M (1979)
This article describes our preliminary results in this field, demonstrating that normal human volunteers respond selectively to two synthetic polypeptide antigens, commonly abbreviated as (TG)-A-L and GAT, which are under Ir gene control in rodents. Some individuals respond to one or the other of the antigens, some to neither, and the occasional individual to both. These results indicate that there are 'responders' and 'nonresponders' just as in previous rodent studies, suggesting that this helper factor assay may be a correlate of human Ir gene function.